Improved Teaching by Changing Approach and Practice - Christian Lindholst, Andrej (Improving University Science Teaching and Learning, 2023)
Compared to previous year’s teaching performance, I attempted to improve this year’s teaching performance by deliberative employment of a new set of teaching tools and changes as a part of a project in the adjunktpædagogikum course given at University of Copenhagen 2011. The tools and changes included problem based learning, careful review and update of materials and lectures, alignment between intended learning outcomes, student activities and evaluation, and employment of a broader set of student activities ranging from engagement in class-room discussions to group based exercises and student presentations. The performance was measured by successive student- and self-evaluations. The student evaluation indicated an improvement in my ability to communicate the course content clearly and precisely and my ability to motivate student reflections on course content. The self-evaluation, based on my perception of the teaching experience, also indicated that the employed changes sustained a higher and more rewarding teaching performance. Reflections upon evaluations also indicated further potentials for improvement.